Is “Bed Sharing” Beneficial and Safe during Infancy? A Systematic Review - Rashmi Ranjan Das; M. Jeeva Sankar; Ramesh Agarwal; Vinod Kumar Paul (International Journal of Pediatrics)
Background. There is conflicting evidence regarding the safety and efficacy of bed sharing during infancy—while it has been shown to facilitate breastfeeding and provide protection against hypothermia, it has been identified as a risk factor for SIDS. Methods. A systematic search of major databases was conducted. Eligible studies were observational studies that enrolled infants in the first 4 weeks of life and followed them up for a variable period of time thereafter. Results. A total of 21 studies were included. Though the quality of evidence was low, bed sharing was found to be associated with higher breastfeeding rates at 4 weeks of age (75.5% versus 50%, OR 3.09 (95% CI 2.67 to 3.58), P=0.043) and an increased risk of SIDS (23.3% versus 11.2%, OR 2.36 (95% CI 1.97 to 2.83), P=0.025). Majority of the studies were from developed countries, and the effect was almost consistent across the studies. Conclusion. There is low quality evidence that bed sharing is associated with higher breast feeding rates at 4 weeks of age and an increased risk of SIDS. We need more studies that look at bed sharing, breast feeding, and hazardous circumstance that put babies at risk.